Lower Cervical Nerve Root Block Using CT Fluoroscopy in Patients with Large Body Habitus: Another Benefit of the Swimmer's Position - Bartynski, W.S. (AJNR Am J Neuroradiol, 2007)
SUMMARY: We describe a method of performing lower cervical nerve root block (CNRB) with CT fluoroscopy in patients with large body habitus using the swimmer's position. This approach reduces image noise with acceptable visualization of vital structures and improved foraminal/root access. Anticipated use of the swimmer's position coupled with minimally modified radiation exposure parameters can limit radiation dose to operator/patient and reduce procedure time to match that of CNRB using CT fluoroscopy in typical patients.